PLANNING SISTEM INFORMASI E-LAUNDRY DENGAN IMPLEMENTASI BERBASIS WEB - Sidratul Munti, Novi Yona; Amri, Zul (Jurnal Pustaka AI (Pusat Akses Kajian Teknologi Artificial Intelligence), 2022)
A laundry business is one that provides washing and ironing services. Laundry is another service-oriented business, and incorporating elements of technology and information into it will make it easier. The good impact of technology in today's business environment is felt not just by large-scale organizations, but also by small and medium-sized businesses that use information and communication technology to manage their operations. In this case, the researcher's title was Design of an E-Laundry Information System with Web-Based Implementation. This website can assist in the efficient operation of the laundry business and make it simple for customers to transact with laundry owners and administrators for data processing. The E-Laundry website will benefit users of laundry services, such as buying services, picking up laundry, and registering arriving clothing and new clients in a timely manner to be delivered to the admin, making it easier for business actors to support their company activities.In this situation, the use of information and communication technology will make business easier, faster, and more dependable, reducing the risk of human error. The goal of this research is to develop a web-based E-Laundry Information System. The method used in this study is the Waterfall method, which has an flow that includes design, analysis, implementation, testing, and maintenance. This system was built with UML (Unified Modeling Language) and the PHP Framework Laravel programming language, which is based on the MYSQL database.